Reputation and Power : Organizational Image and Pharmaceutical Regulation at the FDA - Carpenter, Daniel P., 1967- (Book collections on Project MUSE., 2010)
The U.S. Food and Drug Administration is the most powerful regulatory agency in the world. How did the FDA become so influential? And how exactly does it wield its extraordinary power? Reputation and Power traces the history of FDA regulation of pharmaceuticals, revealing how the agency's organizational reputation has been the primary source of its power, yet also one of its ultimate constraints. Daniel Carpenter describes how the FDA cultivated a reputation for competence and vigilance throughout the last century, and how this organizational image has enabled the agency to regulate an industr.